Youth Slang in Modern English (Journal of Pedagogical Inventions and Practices, 2022)
The article concentrates on the idea of "youth slang" as an essential standard of present-day English language. The creator thinks about the fundamental semantic and elaborate elements of slang, dissect the primary highlights of working and reached the resolution slang is solidly settled in the SMS - correspondence of youngsters as shortenings and abbreviations. The English language, similar to some other, isn't stopping. At present in numerous nations there is a concentrated course of change of the living communicated in language, which is the fundamental point, is the rise of new youth slang